(untitled) (International Seven Journal of Multidisciplinary, 2023)
Cybersecurity in SAP systems technical support is a fundamental concern for enterprises due to the increasing complexity of cyber threats and the crucial role SAP applications play in business operations. Workstations utilized in technical support represent significant attack vectors, particularly during installation, updates, and maintenance procedures. These vulnerabilities, if not properly managed, can lead to unauthorized access, data breaches, and operational disruptions. Ensuring robust security in SAP technical support environments requires a proactive approach that integrates access control, patch management, endpoint protection, and data security measures. This study explores best cybersecurity practices for SAP system technical support, focusing on mitigating workstation vulnerabilities. Key recommendations include implementing multi-factor authentication (MFA) and role-based access control (RBAC) to restrict unauthorized access. The study highlights the necessity of automated patch management systems to reduce exposure to exploit-based attacks and the importance of endpoint protection strategies such as next-generation antivirus solutions and endpoint detection and response (EDR) tools. Furthermore, encryption techniques and data loss prevention (DLP) technologies are identified as crucial measures for safeguarding sensitive business data. A review of recent literature supports these findings, demonstrating how organizations adopting AI-driven security monitoring and zero-trust architectures achieve enhanced cybersecurity resilience. Studies emphasize that traditional security solutions are inadequate in addressing modern cyber threats, advocating for the integration of behavioral-based threat detection and continuous security assessments. In conclusion, enterprises must adopt a multi-layered security approach, combining advanced technical solutions with continuous employee training and proactive threat monitoring. By fostering a security-first culture and refining security frameworks in response to emerging threats, organizations can effectively protect their SAP environments from cyber risks and maintain operational integrity.